Pengembangan Sistem Informasi Layanan Pengurusan Surat dan Pengaduan Aspirasi Warga Berbasis Web di Desa Pagerngumbuk - Muchamad Khafido Ilzam; Adam Hendra Brata; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Pagerngumbuk is a village located in Wonoayu, Sidoarjo. The total population is approximately 3118 people consisting of 1,434 men, 1,684 women, and 920 families spread over 3 hamlets. In Pagerngumbuk Village, there are letter processing services, aspiration complaints services, and village's informations. Problems arise if the Headmen is not at the office because he is on duty outside the city for a long time. Another problem that arises is that there are residents who cannot process documents due to work constraints or living outside the city. Based on the existing problems, a web-based system has developed that can accommodate the residents in conveying aspirations/complaints, managing letters, and delivering village's information in an integrated manner. The system is built using the Waterfall model which then produces 5 types of actors, 69 functional requirements, and 1 non-functional requirement. Whitebox testing uses unit testing of 3 functionals resulting in each path that has been defined can be passed. Blackbox testing uses validation and user acceptance testing, each test produces a 100% valid value. Then compatibility testing on non-functional requirements found several major and minor issues when the system was accessed with an old version browser, but it did not affect on functionality.